2020
DOI: 10.3892/ol.2020.11846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic value of CEA combined with OPN or DKK1 in non‑small cell lung cancer

Abstract: Carcinoma embryonic antigen (CEA), osteopontin (OPN), and Dickkopf-1 (DKK1) expressed in serum are associated with hypoxia in tumor progression. However, the role of these proteins in the plasma of patients with non-small cell lung cancer (NSCLC) is poorly understood. The diagnostic values of CEA combined with OPN or DKK1 were compared in non-small cell lung cancer. This study investigated the diagnostic value of CEA combined with OPN and DKK1, respectively, in NSCLC. Eighty patients with NSCLC (NSCLC group) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In addition, high levels of CEA in the serum are linked to higher TNM stages. A number of studies have found that the preoperative level of CEA is an important independent factor related to the survival of patients with nonsmall cell lung cancer [4,5]. Consistent with previous ndings, the results of this study showed that the level of CEA in the serum was positively correlated with brain metastasis, and was an independent factor of lung cancer brain metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, high levels of CEA in the serum are linked to higher TNM stages. A number of studies have found that the preoperative level of CEA is an important independent factor related to the survival of patients with nonsmall cell lung cancer [4,5]. Consistent with previous ndings, the results of this study showed that the level of CEA in the serum was positively correlated with brain metastasis, and was an independent factor of lung cancer brain metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…At present, tumor markers have been widely used in the early diagnosis, treatment monitoring, and prognostic evaluation of tumors [ 27 , 28 ]. CEA is a nonspecific tumor-associated antigen that is expressed in many types of tumor, but lacks specificity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As CEA is usually produced during fetal development, this stops before birth and CEA is usually not present in the blood of healthy adults. At present, CEA is more commonly applied to the diagnosis of adenocarcinoma in non-small cell lung cancer, but its cut-off level varies greatly in different studies ( 14 , 15 ). In one Chinese study, the serum CEA level of non-small cell lung cancer cases was found to be significantly higher than that of benign lung tumor cases and healthy people ( 16 ), while in another, the level in a lung adenocarcinoma group was significantly higher than that of a lung SCC group and small cell lung cancer group ( 17 ).…”
Section: Discussionmentioning
confidence: 99%